Cultura tributaria y su relación con la gestión de la recaudación de impuesto predial en la Municipalidad Provincial de Requena Loreto 2021 - Meléndez Aspajo, Jairo (2023)
The thesis determined as the main objective the relationship between the tax culture and the collection of property tax in the Provincial Municipality of Requena, Loreto, in addition, I opt for the type of descriptive-correlational study, experimental design, since I take as a study population 342 taxpayers, the collection of information was used as a technique to the survey, as an instrument to the questionnaire. Where, the research concludes that, the tax culture is qualified as average, since the operation of public services is rarely accessible to all taxpayers, likewise, they rarely create values in taxpayers, in addition, the collecting entity rarely uses the media to inform taxpayers about payments, valuable information that improves tax collection. On the other hand, the variable of management of the collection of property tax is qualified as regular, because the institution rarely establishes clear objectives to achieve them, also, that the institution rarely has a properly updated taxpayer registry, which allows it to know who they are, where, the collection unit rarely adequately performs the determination of the tax obligation, finally, the institution rarely performs the correct ordinary collection. On the other hand, it was determined that the tax culture is related to the management of property tax collection with a coefficient of 0.641 Spearman's Rho; as it was also established that tax awareness contrasts a correlation coefficient of 0.547; for tax civic education a correlation coefficient of 0.528; and dissemination of tax guidance a correlation coefficient of 0.522, both are significantly related to the management of property tax collection.